Congress in black and white race and representation in Washington and at home - Grose, Christian R.; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
"Race matters in Congress. This book argues that although electing black legislators yields meaningful outcomes in the lives of African-American voters in the United States, drawing affirmative action districts does not impact policy outcomes for black constituents"--
"The symbolic importance of Barack Obama's election is without question. But beyond symbolism, does the election of African-American politicians matter? Grose argues that it does and presents a unified theory of representation. Electing African-American legislators yields more federal dollars and congressional attention directed toward African-American voters. However, race and affirmative action gerrymandering have no impact on public policy passed in Congress. Grose is the first to examine a natural experiment and exceptional moment in history in which black legislators - especially in the U.S. South - represented districts with a majority of white constituents. This is the first systematic examination of the effect of a legislator's race above and beyond the effect of constituency racial characteristics. Grose offers policy prescriptions, including the suggestion that voting rights advocates, the courts, and redistricters draw "black decisive districts," electorally competitive districts that are likely to elect African Americans"--
Machine generated contents note: 1. African-American legislators, African-American districts, or democrats?; 2. A unified theory of African-American representation in Congress; 3. The "hollow hope" of civil rights change in the US House; 4. Location, location, location: delivering constituency service to African-Americans; 5. Constituency service in the district: connecting black legislators, black staff, and black voters; 6. Bringing home the bacon: delivering federal "pork" to African-Americans; 7. The future of racial redistricting: black decisive districts.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: United States. -- Congress -- Membership; African American legislators; Gerrymandering -- United States; African Americans -- Government policy; Civil rights -- Government policy -- United States; Representative government and representation -- United States; Electronic books